Evidence-based veterinary medicine at 20 – a commentary on historical, philosophical, practical and ethical aspects - David Mills; Michael Reiss; Madeleine Campbell (Veterinary Evidence)
Evidence-based veterinary medicine (EBVM) has pervaded the veterinary profession in the last two decades including academic and regulatory arenas as well as practising veterinary surgeons. EBVM grew from its older human sister, evidence-based medicine (EBM) and in doing so shares EBM’s central tenets of how best to do medicine. However, EBM has by no means been universally accepted; it has attracted fierce criticism and undergone several revisions since inception. In this article, we trace history of both movements and critically examine the philosophical basis of EBM/EBVM being better. We also assess the practicality of EBVM and examine ethical aspects of its use. With knowledge of EBM’s evolution, possible ways forward for EBVM are suggested that attempt to avoid EBM’s historical setbacks and improve individual veterinary patient care under EBVM.